Analysis of key variables for energy efficiency in warships. (February 2020) - Carrasco, Pedro; Bendaña, Ricardo; Paredes, Angel; Michinel, Humberto; Fernández de Córdoba, Pedro; Arce, M Elena; Zaragoza, Sonia
The purpose of this work is to investigate the effect of environmental variables on the electric energy expenditure of a typical surface warship. Studies with similar objectives are much more frequent for merchant ships, but warship operations have peculiarities that will be emphasised. In particular, they spend large fractions of their life cycle at port, during which the vessel remains active. First, a discussion of the embarked systems is presented, pointing out the importance of auxiliary systems and, in particular, heating, ventilation and air conditioning. Quantitative estimates of the energy consumption of those systems are provided. Then, using data taken during real operations of a frigate of the Spanish Navy, correlations are computed between power consumption and different environmental variables. As a novelty, the analysis is carried out separating the different modes of operation of the ship. This leads to interesting conclusions, including a considerable positive correlation between seawater temperature and fuel consumption when the vessel is in port. The effect of a moored ship on the surrounding seawater temperature is studied by a numerical computation. The results suggest that the position of sea chests may be consequential for energy efficiency.